Linking natural resource governance to rural livelihoods and wildlife conservation : a case study of Mufunta game management area, Zambia - Hachoofwe, Emelda Miyanda (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.